The complete chloroplast genome of Pollia japonica (Commelinaceae) from Southeast China - Gu, Ye (Mitochondrial DNA B Resour, 2021)
The complete chloroplast genome of Pollia japonica, a medicinal herb native to East Asia was characterized. The size of the chloroplast genome is 165,076 bp in length with a large single copy (LSC) of 90,722 bp, a small single copy (SSC) of 19,146 bp, and a pair of inverted repeats of 27,604 bp. The chloroplast genome encodes a set of 131 genes, including 85 protein-coding, 38 tRNAs, and 8 rRNAs. Phylogenetic analysis based on complete chloroplast genomes validated the phylogenetic position of P. japonica and showed that the six species from Commelinales were fully resolved in a monophyletic clade sister to the Zingiberales. Species from the Zingiberales and Commelinales formed a molophyletic group sister to the Poales. The chloroplast genome of P. japonica provides an important resource for further study of molecular evolution in the Commelinaceae.